Production and Exchange among Wemindji Cree: Egalitarian Ideology and Economic Base - Scott, Colin (Culture, 1982)
Despite a series of changes in productive forces and in relations with capitalist society, the Cree of northern Quebec have maintained a domestic mode of production. Until quite recently, reciprocity was seriously entertained as the idiom of relations even with the white man. This paper examines, for Wemindji Cree hunters, the effect of increased consumer affluence on subsistence production, sharing, and potential stratification between subsistence-oriented and wage-earning sectors of the local economy. The case of Wemindji Cree suggests that “antisurplus” forces in a domestic mode of production are reduced when domestic producers enter into reciprocal exchange with wage-earners, who have superior access to consumer goods. Surplus bush product is generated by domestic producers in exchange for help from wage-earning relatives in purchasing labor-saving technology and other consumer items. Hence, inequalities of access to both bush products and consumer goods are reduced or eliminated. However, for ecological and technological reasons, possible increases in domestic productivity are often more restricted than potential increases in wage income. Egalitarian exchange is threatened if wage-earners’ margin of superior access to consumer goods becomes disproportionate to domestic producers’ ability to produce a parallel surplus of bush products. In that case, the ideology of reciprocity would require that the value of domestic products become too marked, wage-earners might not exchange enough of their goods for equality to obtain, and permanent stratification might develop. A second scenario consists in the establishment of independent access to more consumer goods for domestic producers (in addition to legal guarantees of a subsistence base). In the James Bay and Northern Quebec Agreement (1975), this condition was established in the form of a guaranteed annual income for hunters.